Antioxidative constituents from petroleum ether extract of curcuma longa leaves / Nurhidayah Osman and Aiza Harun - Osman, Nurhidayah; Harun, Aiza (Universiti Teknologi MARA Cawangan Pahang, 2019)
Curcuma longa which is traditionally known as turmeric is a well-known plant species with valued medicinal purposes as well as an ingredient in food industry. Curcuma longa leaves were believed to contain secondary metabolites with amazing antioxidant properties. Thin layer chromatographic (TLC) technique was implemented to screen antioxidative phytochemicals and preparative thin layer chromatography for isolation purposes. The identification of antioxidative constituents was performed using Gas Chromatography Mass Spectrometer (GCMS) with Wiley database matching individually. TLC screening which revealed petroleum ether extract has higher contribution of antioxidative constituents compared to dichloromethane and methanol extracts and hence it was selected for isolation process of antioxidative constituents. GCMS analysis proposed antioxidative constituents from C.longa leaves as (A) (2,4cyclopentadien-1-ylidenemethyl) benzene, (B)1,3-dimethyl benzene,(C)Estra-1,3,5(10)-trien-17β-ol,(D)1-methylene-1HIndene,(E)1methylcyclopentanol after analyzing with GCMS aided with Wiley Database matching individually. According to its potent antioxidant properties, the use of C. longa leaves should be taking into consideration in the development of new natural medicine for the treatment of various diseases.